KNOWLEDGE, ATTITUDE, AND BEHAVIOR OF MOTHERS' HANDS WASHING WITH SOAP WITH DIARRHEA AMONG CHILDREN UNDER FIVE - Suryani, Dyah; Muplihah, Siti; Suyitno, Suyitno (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Diarrhea is a prevalent health issue among infants, particularly between the ages of 6 months and 2 years, as well as in children under five. Various factors contribute to the occurrence of diarrhea in infants, one of which is the mother's handwashing behavior. This behavior can be influenced by several factors, including knowledge and attitudes. This study aims to explore the relationship between mothers' knowledge, attitudes, and handwashing behaviors with soap, and the incidence of diarrhea in infants in Dusun Kanoman and Dusun Dukuh, Banyuraden Village, Gamping Subdistrict, Sleman District, Yogyakarta Province, Indonesia. This cross-sectional study involved a population of mothers with children aged 0-24 months, with a total sample size of 72 respondents, selected through total sampling. The research instruments included questionnaires assessing knowledge, attitudes, behaviors, and the occurrence of diarrhea. Data were analyzed using the Chi-square test. The results indicated no significant relationship between the level of knowledge of handwashing with soap and the occurrence of diarrhea (p-value = 0.218). Similarly, there was no significant relationship between mothers' attitudes towards handwashing with soap and the incidence of diarrhea (p-value = 0.821), nor between handwashing behavior and the occurrence of diarrhea (p-value = 0.644). The study concludes that there is no correlation between mothers' knowledge, attitudes, and handwashing behaviors with soap and the incidence of diarrhea in infants within the study population.